A Young Female with Difficulty in Blood Group Determination (Journal of Medicine, 2017)
Cold agglutinin disease (CAD) usually develops as a result of the production of a specific immunoglobulin M auto-antibody directed against the I/i and H antigens, precursors of the ABH and Lewis blood group substances, on red blood cells. Where most of the cases of cold agglutination disease usually present with features of hemolysis, acrocyanosis, respiratory symptoms or fatigue due to anemia, here we report an interesting case of CAD with unusual presentation.This 26 years female came with fever for 10 days,jaundice for two months and failure in blood group determination for blood transfusion for her anemia.The physical examination showed severe pallor, jaundice, hepatosplenomegaly and fundoscopic examination revealed Roth spots, hemorrhages and bilateral papilloedema with otherwise normal neurological examination.Complete blood count revealed severe anemia, spuriously raised MCV and MCHC with raised ESR. Peripheral blood film features were suggestive of autoimmune hemolytic anemia (Cold agglutinin disease). MRI of brain was normal. It further indicates the various manifestation of disease as in here presenting as papilloedema in patients with cold agglutination diseaseJ MEDICINE January 2017; 18 (1) : 39-41